Electrodeposition preparation method of electrolytic water anode material loaded with transition metal oxyhydroxide
Through the electrodeposition preparation method of electrolytic water anode material supported by transition metal hydroxyoxide, the existing OER catalyst has been solved, and an efficient and stable electrolytic oxygen evolution reaction catalyst has been achieved.
Patent Information
- Application Number
- CN202510308150.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-05-02
AI Technical Summary
Existing electrolytic oxygen-induced reaction (OER) catalysts are expensive and have poor stability under certain conditions, making it difficult to meet low-cost and efficient needs.
The electrolytic water anode material loaded with transition metal hydroxyoxide was prepared by electrodeposition preparation method, and the electrolytic water anode material loaded with transition metal hydroxyoxide was prepared by direct current electroplating technology.
The prepared electrolytic water anode material with a transition metal hydroxyoxide loading exhibits excellent stability and OER performance, and is simple in preparation, short in time and high in efficiency, and is suitable for industrial production.
Smart Images

Figure CN119913546A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalytic hydrogen evolution, and in particular to an electrodeposition preparation method of a water electrolysis anode material loaded with a transition metal oxyhydroxide. Background Art
[0002] With the rapid development of global science and technology and the continuous growth of population, people's demand for energy is increasing. However, the fossil fuel resources that people currently rely on are not only limited in quantity, but also the greenhouse gases such as carbon dioxide produced by their combustion exacerbate the problem of global warming. Therefore, it has become a top priority to develop clean and sustainable energy technologies and reduce dependence on fossil fuels. As an important link in the process of hydrogen production by electrolysis of water, the study of oxygen evolution by electrolysis of water is of great significance to promoting the development of the hydrogen energy economy.
[0003] In the process of water electrolysis, oxygen evolution reaction (OER) is a key half-reaction. Its reaction kinetics are relatively slow, the reaction energy barrier is high, and it can only occur at a higher overpotential, which seriously reduces the efficiency of electricity-hydrogen fuel conversion. Therefore, the development of efficient and stable oxygen evolution reaction catalysts is crucial to improve the efficiency of hydrogen production by water electrolysis.
[0004] Currently, the best OER catalysts are iridium oxide and ruthenium oxide, but they are expensive and have poor stability under certain conditions. Therefore, researchers are committed to developing low-cost and efficient transition metal-based OER electrocatalysts, such as cobalt, nickel, and iron. These materials not only have good catalytic performance, but also have high environmental adaptability and long-term stability.
[0005] In view of the above reasons, providing a method for preparing an electrolytic water electrolysis anode material loaded with transition metal hydroxide oxide has become a technical problem to be solved urgently by those skilled in the art. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing an electrolytic water anode material loaded with transition metal hydroxide oxides through electrodeposition. The method for preparing an electrolytic water anode material loaded with transition metal hydroxide oxides through electrodeposition has a simple preparation process, short time, high efficiency, and easy control and adjustment of reaction conditions. The prepared electrolytic water anode material loaded with transition metal hydroxide oxides exhibits excellent stability and OER performance.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] One of the technical solutions of the present invention:
[0009] A method for preparing an electrolytic water anode material loaded with a transition metal oxyhydroxide by electrodeposition comprises the following steps:
[0010] 1) placing the nickel foam in a hydrochloric acid solution and subjecting it to ultrasonic treatment to remove oxidized impurities on the surface of the nickel foam, thereby obtaining a nickel foam carrier;
[0011] 2) adding the main salt, boric acid, sodium chloride and ammonium chloride into ultrapure water, and dissolving them by ultrasonication to obtain an electroplating solution;
[0012] 3) placing the nickel foam carrier obtained in step 1) in the electroplating solution obtained in step 2), and performing direct current electroplating on the nickel foam carrier to obtain the water electrolysis anode material loaded with transition metal hydroxide.
[0013] Furthermore, in step 1), the size of the nickel foam is 1 cm×1.5 cm.
[0014] Furthermore, in step 1), the concentration of the hydrochloric acid solution is 3 mol / L.
[0015] Furthermore, in step 1), the ultrasonic treatment is specifically: first soaking in a hydrochloric acid solution for 10 minutes, and then ultrasonic treatment for 5 minutes.
[0016] Furthermore, in step 1), after the ultrasonic treatment, the nickel foam after the ultrasonic treatment needs to be cleaned and dried.
[0017] Furthermore, the cleaning is specifically as follows: placing the nickel foam after ultrasonic treatment in anhydrous ethanol and ultrapure water in turn, and ultrasonic cleaning for 5 minutes.
[0018] Furthermore, in step 2), the main salt includes any two of nickel salt, cobalt salt and iron salt.
[0019] Furthermore, in step 2), in the obtained electroplating solution, the concentrations of the main salt, boric acid, sodium chloride and ammonium chloride are 0.56 mol / L, 0.7 mol / L, 0.37 mol / L and 0.47 mol / L, respectively.
[0020] Furthermore, in step 2), the duration of the ultrasonic dissolution is 10 minutes.
[0021] Furthermore, in step 3), the direct current electroplating is specifically: controlling the current density to be 500-2300 mA / cm 2 , electroplating 30 to 180 seconds.
[0022] Furthermore, in step 3), after the direct current electroplating, the foamed nickel carrier after the direct current electroplating needs to be washed with ultrapure water and dried.
[0023] The second technical solution of the present invention:
[0024] The anode material for electrolysis of water loaded with transition metal oxyhydroxide is prepared by the electrodeposition preparation method of the anode material for electrolysis of water loaded with transition metal oxyhydroxide.
[0025] The third technical solution of the present invention:
[0026] Application of the above-mentioned water electrolysis anode material loaded with transition metal hydroxide oxide in hydrogen production by seawater electrolysis.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention provides an electrodeposition preparation method for a water electrolysis anode material loaded with a transition metal hydroxide oxide, which has a simple preparation process, short time, high efficiency, and easy control and adjustment of reaction conditions, and is suitable for industrial production.
[0029] The present invention provides an electrodeposition preparation method for an electrolytic water splitting anode material loaded with transition metal hydroxide oxides. The electroplating process is used to load transition metal iron, cobalt, and nickel hydroxide oxides (including FeNiOOH, FeCoOOH, and NiCoOOH), so that the transition metal iron, cobalt, and nickel hydroxide oxides have more active sites and better stability on the nickel foam carrier, so that the finally prepared electrolytic water splitting anode material loaded with transition metal hydroxide oxides exhibits excellent stability and OER performance.
[0030] The present invention provides a method for preparing an electrolytic water splitting anode material loaded with transition metal hydroxide. The prepared electrolytic water splitting anode material loaded with transition metal hydroxide has a porous structure and a large specific surface area, which significantly increases the contact area of the electrolyte, is beneficial to the diffusion of the electrolyte, promotes the mass transfer process, and effectively improves the OER performance of the electrolytic water splitting anode material loaded with transition metal hydroxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0032] Figure 1 This is the SEM image of FeN iOOH prepared in Example 1;
[0033] Figure 2 This is the in-situ Raman spectrum of FeN iOOH prepared in Example 1;
[0034] Figure 3 This is the in-situ Raman spectrum of FeCoOOH prepared in Example 2;
[0035] Figure 4 This is the in-situ Raman spectrum of NiCoOOH prepared in Example 3;
[0036] Figure 5 The XPS graphs of FeNiOOH, FeCoOOH and NiCoOOH prepared in Examples 1 to 3, wherein A is the XPS graph of the Ni element, B is the XPS graph of the Co element, and C is the XPS graph of the Fe element;
[0037] Figure 6 This is a comparison chart of the OER performance of FeNiOOH, FeCoOOH and NiCoOOH prepared in Examples 1 to 3;
[0038] Figure 7 The OER performance diagram of the water electrolysis anode material loaded with iron-nickel bimetallic element and iron-nickel bimetallic oxide prepared in Comparative Examples 1 to 2;
[0039] Figure 8 This is a stability comparison chart of FeNiOOH, FeCoOOH and NiCoOOH prepared in Examples 1 to 3. DETAILED DESCRIPTION
[0040] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0041] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0045] In the following examples and comparative examples, all the raw materials used were commercially available.
[0046] In the following embodiments, a method for preparing an electrolytic water electrolysis anode material loaded with a transition metal oxyhydroxide by electrodeposition comprises the following steps:
[0047] 1) placing the nickel foam in a hydrochloric acid solution and performing ultrasonic treatment to remove oxidized impurities on the surface of the nickel foam, then washing the nickel foam after the ultrasonic treatment and drying at room temperature to obtain a nickel foam carrier;
[0048] Wherein, the specification of the nickel foam is 1cm×1.5cm;
[0049] Wherein, the concentration of the hydrochloric acid solution is 3 mol / L;
[0050] The ultrasonic treatment is specifically as follows: first soaking in a hydrochloric acid solution for 10 minutes, and then ultrasonic treatment for 5 minutes;
[0051] The cleaning is specifically as follows: placing the nickel foam after ultrasonic treatment in anhydrous ethanol and ultrapure water in turn, and ultrasonically cleaning for 5 minutes;
[0052] 2) adding the main salt, boric acid, sodium chloride and ammonium chloride into ultrapure water, and dissolving them by ultrasonication to obtain an electroplating solution;
[0053] Wherein, the main salt includes any two of nickel salt, cobalt salt and iron salt;
[0054] Wherein, in the obtained electroplating solution, the concentrations of the main salt, boric acid, sodium chloride and ammonium chloride are 0.56 mol / L, 0.7 mol / L, 0.37 mol / L and 0.47 mol / L respectively;
[0055] Wherein, the duration of the ultrasonic dissolution is 10 min;
[0056] 3) placing the nickel foam carrier obtained in step 1) in the electroplating solution obtained in step 2), performing direct current electroplating on the nickel foam carrier, then washing it three times with ultrapure water, and drying it to obtain the water electrolysis anode material loaded with transition metal hydroxide;
[0057] The direct current electroplating is specifically as follows: controlling the current density to be 500-2300 mA / cm 2 , electroplating 30 to 180 seconds.
[0058] Example 1
[0059] A kind of electrolytic water anode material loaded with transition metal iron and nickel hydroxide
[0060] 1) placing nickel foam (NF, 1 cm×1.5 cm) in a hydrochloric acid solution with a concentration of 3 mol / L and performing ultrasonic treatment to remove oxidized impurities on the surface of the nickel foam, then washing the nickel foam after the ultrasonic treatment and drying at room temperature to obtain a nickel foam carrier;
[0061] The ultrasonic treatment is specifically as follows: first soaking in a hydrochloric acid solution for 10 minutes, and then ultrasonic treatment for 5 minutes;
[0062] The cleaning is specifically as follows: placing the nickel foam after ultrasonic treatment in anhydrous ethanol and ultrapure water in turn, and ultrasonically cleaning for 5 minutes;
[0063] 2) adding 17 g of nickel sulfate hexahydrate, 17 g of ferric chloride hexahydrate, 5 g of boric acid, 2.5 g of sodium chloride and 2.87 g of ammonium chloride to 115 mL of ultrapure water, and dissolving by ultrasonication for 10 min to obtain an electroplating solution;
[0064] 3) placing the nickel foam carrier obtained in step 1) in the electroplating solution obtained in step 2), performing direct current electroplating on the nickel foam carrier, then washing it three times with ultrapure water, and drying it to obtain the electrolytic water anode material loaded with transition metal iron and nickel hydroxide, which is recorded as FeNiOOH;
[0065] The DC electroplating process is as follows: the current density is controlled to be 2300 mA / cm 2 , electroplating 35s.
[0066] Example 2
[0067] Anode materials for water electrolysis loaded with transition metal iron and cobalt hydroxide
[0068] 1) placing nickel foam (NF, 1 cm×1.5 cm) in a hydrochloric acid solution with a concentration of 3 mol / L and performing ultrasonic treatment to remove oxidized impurities on the surface of the nickel foam, then washing the nickel foam after the ultrasonic treatment and drying at room temperature to obtain a nickel foam carrier;
[0069] The ultrasonic treatment is specifically as follows: first soaking in a hydrochloric acid solution for 10 minutes, and then ultrasonic treatment for 5 minutes;
[0070] The cleaning is specifically as follows: placing the nickel foam after ultrasonic treatment in anhydrous ethanol and ultrapure water in turn, and ultrasonically cleaning for 5 minutes;
[0071] 2) adding 17 g of ferric chloride hexahydrate, 15 g of cobalt chloride hexahydrate, 5 g of boric acid, 2.5 g of sodium chloride and 2.87 g of ammonium chloride to 115 mL of ultrapure water, and dissolving by ultrasonication for 10 min to obtain an electroplating solution;
[0072] 3) placing the nickel foam carrier obtained in step 1) in the electroplating solution obtained in step 2), performing direct current electroplating on the nickel foam carrier, then washing it three times with ultrapure water, and drying it to obtain the electrolytic water anode material loaded with transition metal iron and cobalt hydroxide, which is recorded as FeCoOOH;
[0073] The DC electroplating process is as follows: the current density is controlled to be 2300 mA / cm 2 , electroplating 35s.
[0074] Example 3
[0075] Anode materials for water electrolysis loaded with transition metal nickel and cobalt hydroxide
[0076] 1) placing nickel foam (NF, 1 cm×1.5 cm) in a hydrochloric acid solution with a concentration of 3 mol / L and performing ultrasonic treatment to remove oxidized impurities on the surface of the nickel foam, then washing the nickel foam after the ultrasonic treatment and drying at room temperature to obtain a nickel foam carrier;
[0077] The ultrasonic treatment is specifically as follows: first soaking in a hydrochloric acid solution for 10 minutes, and then ultrasonic treatment for 5 minutes;
[0078] The cleaning is specifically as follows: placing the nickel foam after ultrasonic treatment in anhydrous ethanol and ultrapure water in turn, and ultrasonically cleaning for 5 minutes;
[0079] 2) adding 17 g of nickel sulfate hexahydrate, 15 g of cobalt chloride hexahydrate, 5 g of boric acid, 2.5 g of sodium chloride and 2.87 g of ammonium chloride to 115 mL of ultrapure water, and dissolving by ultrasonication for 10 min to obtain an electroplating solution;
[0080] 3) placing the nickel foam carrier obtained in step 1) in the electroplating solution obtained in step 2), performing direct current electroplating on the nickel foam carrier, then washing it three times with ultrapure water, and drying it to obtain the electrolytic water anode material loaded with transition metal nickel and cobalt hydroxide, which is recorded as Ni CoOOH;
[0081] The DC electroplating process is as follows: the current density is controlled to be 2300 mA / cm 2 , electroplating 35s.
[0082] Comparative Example 1
[0083] A water electrolysis anode material loaded with iron-nickel bimetallic element
[0084] 1) placing nickel foam (NF, 1 cm×1.5 cm) in a hydrochloric acid solution with a concentration of 3 mol / L and performing ultrasonic treatment to remove oxidized impurities on the surface of the nickel foam, then washing the nickel foam after the ultrasonic treatment and drying at room temperature to obtain a nickel foam carrier;
[0085] The ultrasonic treatment is specifically as follows: first soaking in a hydrochloric acid solution for 10 minutes, and then ultrasonic treatment for 5 minutes;
[0086] The cleaning is specifically as follows: placing the nickel foam after ultrasonic treatment in anhydrous ethanol and ultrapure water in turn, and ultrasonically cleaning for 5 minutes;
[0087] 2) adding 17 g of nickel sulfate hexahydrate, 17 g of ferric chloride hexahydrate, 5 g of boric acid, 2.5 g of sodium chloride and 2.87 g of ammonium chloride to 115 mL of ultrapure water, and dissolving by ultrasonication for 10 min to obtain an electroplating solution;
[0088] 3) placing the nickel foam carrier obtained in step 1) in the electroplating solution obtained in step 2), performing direct current electroplating on the nickel foam carrier, then washing it three times with ultrapure water, and drying it to obtain the electrolytic water anode material loaded with the iron-nickel bimetallic element;
[0089] The direct current electroplating is specifically as follows: the current density is controlled to be 20 mA / cm 2 , electroplating 1200s.
[0090] Comparative Example 2
[0091] A water electrolysis anode material loaded with iron-nickel bimetallic oxide
[0092] 1) placing nickel foam (NF, 1 cm×1.5 cm) in a hydrochloric acid solution with a concentration of 3 mol / L and performing ultrasonic treatment to remove oxidized impurities on the surface of the nickel foam, then washing the nickel foam after the ultrasonic treatment and drying at room temperature to obtain a nickel foam carrier;
[0093] The ultrasonic treatment is specifically as follows: first soaking in a hydrochloric acid solution for 10 minutes, and then ultrasonic treatment for 5 minutes;
[0094] The cleaning is specifically as follows: placing the nickel foam after ultrasonic treatment in anhydrous ethanol and ultrapure water in turn, and ultrasonically cleaning for 5 minutes;
[0095] 2) adding 17 g of nickel sulfate hexahydrate, 17 g of ferric chloride hexahydrate, 5 g of boric acid, 2.5 g of sodium chloride and 2.87 g of ammonium chloride to 115 mL of ultrapure water, and dissolving by ultrasonication for 10 min to obtain an electroplating solution;
[0096] 3) placing the nickel foam carrier obtained in step 1) in the electroplating solution obtained in step 2), performing direct current electroplating on the nickel foam carrier, then washing it three times with ultrapure water, and drying it to obtain the electrolytic water anode material loaded with iron-nickel bimetallic oxide;
[0097] The DC electroplating is specifically as follows: the current density is controlled to be 130 mA / cm 2 , electroplating 600s.
[0098] Effect verification:
[0099] The transition metal hydroxide-loaded water electrolysis anode material prepared in Example 1 was subjected to SEM analysis. The SEM image of FeNiOOH prepared in Example 1 is as follows: Figure 1 As shown;
[0100] Depend on Figure 1 It can be seen that the FeNiOOH prepared in Example 1 is evenly covered on the Ni foam substrate and has a porous structure and a larger specific surface area.
[0101] The in-situ Raman spectroscopic analysis of the transition metal hydroxide-loaded water electrolysis anode material prepared in Examples 1 to 3 showed that the in-situ Raman spectra of the transition metal hydroxide-loaded water electrolysis anode material were as follows: Figures 2 to 4 As shown, Figure 2 This is the in-situ Raman spectrum of FeNiOOH prepared in Example 1. Figure 3 This is the in-situ Raman spectrum of FeCoOOH prepared in Example 2. Figure 4 This is the in-situ Raman spectrum of Ni CoOOH prepared in Example 3;
[0102] Depend on Figures 2 to 4 It can be seen that the electrodeposition preparation method provided by the present invention can directly synthesize bimetallic oxyhydroxides, and the peak value does not move with the increase of voltage, which indicates that the FeNiOOH prepared by the present invention has good stability; in addition, Figure 2 480cm in -1 and 542cm -1 There is an obvious peak, which indicates that FeNiOOH is successfully synthesized. Figure 3 Medium 490cm -1 and 564cm -1 There is an obvious peak at , which indicates that FeCoOOH is successfully synthesized. Figure 4 Medium 473cm -1 and 550cm -1 An obvious new peak appeared at , which indicated that Ni CoOOH was successfully synthesized.
[0103] The transition metal hydroxide-loaded water electrolysis anode materials prepared in Examples 1 to 3 were subjected to X-ray photoelectron spectroscopy analysis. The XPS graphs of FeNiOOH, FeCoOOH and NiCoOOH prepared in Examples 1 to 3 are as follows: Figure 5 As shown, A is the XPS graph of Ni element, B is the XPS graph of Co element, and C is the XPS graph of Fe element;
[0104] Depend on Figure 5 It can be seen that the electrodeposition preparation method provided by the present invention can directly synthesize bimetallic oxyhydroxides, and there is electron transfer between Fe and Ni and Co. The incorporation of Fe causes a significant increase in the content of high-valent substances in Ni and Co, generates more oxyhydroxides, and exhibits better OER performance, while there is no electronic interaction between Ni and Co, and no electron transfer exists.
[0105] The OER performance test was performed on the transition metal hydroxide-loaded water electrolysis anode materials prepared in Examples 1 to 3. The OER performance test was specifically as follows:
[0106] Using an electrolytic cell as a container, the anode material for electrolysis of water loaded with transition metal hydroxide prepared in Examples 1 to 3 as a working electrode, a platinum wire as an auxiliary electrode, an Ag / AgCl electrode as a reference electrode, and a KOH solution with a concentration of 1 mol / L as an electrolyte, an electrochemical workstation was used to test the OER performance of the anode material for electrolysis of water loaded with transition metal hydroxide prepared in Examples 1 to 3;
[0107] OER performance test conditions: temperature: room temperature, LSV scan rate: 10mV / s, LSV test voltage range: 0~1.2V;
[0108] The OER performance comparison of FeNiOOH, FeCoOOH and NiCoOOH prepared in Examples 1 to 3 is shown in the figure Figure 6 Show;
[0109] Depend on Figure 6 It can be seen that Fe-Ni-based and Fe-Co-based water electrolysis anode materials have excellent OER performance compared with Ni-Co-based water electrolysis anode materials, and Fe-Ni-based and Fe-Co-based water electrolysis anode materials have excellent OER performance at a current density of 100 mA / cm 2 The overpotential is 0.29V.
[0110] The OER performance test was performed on the water electrolysis anode materials loaded with iron-nickel bimetallic elements and iron-nickel bimetallic oxides prepared in Comparative Examples 1 to 2, and the specific OER performance test method was the same as above;
[0111] The OER performance comparison of the prepared iron-nickel bimetallic element and iron-nickel bimetallic oxide electrolytic water anode materials prepared in Comparative Examples 1 to 2 is shown in the figure Figure 7 Show.
[0112] The stability of the water electrolysis anode materials loaded with transition metal hydroxide prepared in Examples 1 to 3 was tested. The stability comparison of FeNiOOH, FeCoOOH and NiCoOOH prepared in Examples 1 to 3 is shown in the figure below: Figure 8 Show;
[0113] Depend on Figure 8 It can be seen that FeNiOOH and FeCoOOH have good stability and can be 2 It can run stably for 100 h at a current density of , while the stability of NiCoOOH is relatively poor.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing an electrolytic water anode material loaded with a transition metal oxyhydroxide by electrodeposition, characterized in that: The following steps are involved: 1) placing the nickel foam in a hydrochloric acid solution and subjecting it to ultrasonic treatment to remove oxidized impurities on the surface of the nickel foam, thereby obtaining a nickel foam carrier; 2) adding the main salt, boric acid, sodium chloride and ammonium chloride into ultrapure water, and dissolving them by ultrasonication to obtain an electroplating solution; 3) placing the nickel foam carrier obtained in step 1) in the electroplating solution obtained in step 2), and performing direct current electroplating on the nickel foam carrier to obtain the water electrolysis anode material loaded with transition metal hydroxide.
2. The method for preparing a water electrolysis anode material loaded with transition metal oxyhydroxide by electrodeposition according to claim 1, characterized in that: In step 1), the concentration of the hydrochloric acid solution is 3 mol / L.
3. The method for preparing the electrolytic water anode material loaded with transition metal oxyhydroxide according to claim 1, characterized in that: In step 1), the ultrasonic treatment is specifically: first soaking in a hydrochloric acid solution for 10 minutes, and then ultrasonic treatment for 5 minutes.
4. The method for preparing the electrolytic water anode material loaded with transition metal oxyhydroxide according to claim 1, characterized in that: After the ultrasonic treatment, the nickel foam after the ultrasonic treatment needs to be cleaned and dried.
5. The method for preparing the electrolytic water anode material loaded with transition metal oxyhydroxide according to claim 4, characterized in that: The cleaning is specifically as follows: placing the nickel foam after ultrasonic treatment in anhydrous ethanol and ultrapure water in turn, and ultrasonically cleaning for 5 minutes.
6. The method for preparing the electrolytic water anode material loaded with transition metal oxyhydroxide according to claim 1, characterized in that: In step 2), the main salt includes any two of nickel salt, cobalt salt and iron salt.
7. The method for preparing the electrolytic water anode material loaded with transition metal oxyhydroxide according to claim 1, characterized in that: In step 2), in the obtained electroplating solution, the concentrations of the main salt, boric acid, sodium chloride and ammonium chloride are 0.56 mol / L, 0.7 mol / L, 0.37 mol / L and 0.47 mol / L respectively.
8. The method for preparing the electrolytic water anode material loaded with transition metal oxyhydroxide according to claim 1, characterized in that: In step 3), the direct current electroplating is specifically as follows: controlling the current density to be 500-2300 mA / cm 2 , electroplating 30 to 180 seconds.
9. An anode material for electrolysis of water loaded with a transition metal oxyhydroxide prepared by the electrodeposition preparation method for an anode material for electrolysis of water loaded with a transition metal oxyhydroxide as claimed in any one of claims 1 to 8.
10. Use of the water electrolysis anode material loaded with transition metal oxyhydroxide as claimed in claim 9 in hydrogen production by seawater electrolysis.